CP-063 Ustekinumab: Treatment persistence. (14th February 2016) - Guerra, M; Ruano, R; Medina, J; Urbina, J Ortiz de; Gutierrez, E; Saez, M; Almendral, ML; Rico, B
Abstract : Background: Persistence can predict treatment success and is affected by different factors, such as efficacy, safety, cost and other factors related to the patient. Purpose: The objective of this study was to assess persistence of treatment with ustekinumab in patients in a tertiary university hospital, and the causes of discontinuation. Material and methods: Retrospective observational study of patients treated at our centre with ustekinumab from January 2009 to September 2015. The persistence of treatment was defined as the time (days) from the date of the first dispensation to one of the following cases: treatment interruption, change or deadline for data entry (30 September 2015). Data were collected from dispensing records to outpatients and review of their medical records. Results: 49 patients (22 women and 27 men) were reviewed. The diagnosis was psoriasis (PS) in 71.4% of cases, Crohn's disease/ulcerative colitis (CD/UC) in 24.5% and psoriatic arthritis (PA) in 4.1%. 32 patients had been treated with anti-TNF (infliximab, adalimumab, etanercept) and all had undergone prior treatment with immunosuppressants. The average treatment duration of patients that were undergoing active treatment as of 30 September 2015 was 942.3 days (PS=977.2, CD/UC=868.8, PA=370). The average number of units dispensed to these patients was 16.4. 26.5% of patients discontinued treatment: 46.2% of them had been diagnosed with CD/UC, 46.2% with PS and 7.7% with PA. The average treatment duration was 364.23 days (PS=325.8, CD/UC=460.8, PA=28). The average numer of units dispensed to these patients was 11.1. 16.7% of patients with PS discontinued treatment after 325.83 days, 50% of patients with CD/UC after 460.8 days and 50% of patients with PA after 28 days. 13 patients discontinued treatment for the following reasons: inefficiency (6), tolerance or adverse effects related problems (2): 1 case of generalised CMV infection and 1 case of recurrent flu-like syndrome and loss of strength in a limb; exitus (2): 1 because of advanced age and 1 because of colon cancer; 1 had moved to another city (1), 1 for personal reasons (1) and 1 for unknown reasons (1). Conclusion: 26.5% of patients discontinued treatment with ustekinumab after a period of less than 1 year. The treatment persistence of PS with ustekinumab appears to be greater than the treatment persistence of CD/UC persistence. The results obtained for PA patients cannot be considered representative as there were only two patients. The main cause of non-persistence is treatment failure, followed by tolerance or side effects related problems. These data do not match the literature, and a longer tracking will be necessary to clarify whether this drug has higher or lower persistence than other biological alternatives. References and/or Acknowledgements: We thank Francisco Bautista for his assistance with translation as proofreader No conflict of interest.